Captain Wag the pirate dog - Terry, Michael (London : Bloomsbury, 2007)
Captain Wag can not believe his luck - he has found a treasure map! Without more ado he and his fellow shipmates One-Eye Jack and Old Scratch, take to the high seas to track down the treasure ....
Keywords: Adventure -- Fiction; Pirates -- Fiction; Treasures -- Fiction